MANAGEMENT OF SYSTEM OF PREPARATION OF HIGH QUALIFICATION WRESTLERS WITH USE INNOVATIVE PEDAGOGICAL TECHNOLOGIES - Saidov Izzatillo Istаmovich (International Journal of Advanced Science and Technology, 2020)
In article was written about useful methods of pedagogical technologies in teaching and preparing physical training and its importance in wrestling competitions.